Zamantı Yöresi Oksit Kurşun-çinko Cevherlerinin Zenginleştirilmesi - Engin, Aykut (Fen Bilimleri Enstitüsü, 2015)
Kayseri-Zamantı bölgesinde bulunan oksit kurşun-çinko cevherlerinin selektif olarak zenginleştirilmesi bu tezin konusunu oluşturmaktadır. Karışım numunesinin ilk olarak fiziksel kimyasal ve mineralojik özellikleri belirlenmiştir. Yapılan orijinal boyut dağılımı analizinde, malzemenin %65’e yakın bir kısmının 3.36 mm altında olduğu saptanmıştır. Karışım numunesi, %11.50 Zn ve %9.81 Pb içermektedir. Flotasyon ön deneylerinde kurşun için en iyi sonuç; doğal pH, 0.1 mm altı boyut ve %25 PKO olarak belirlenmiştir. MGS ile yapılan deneylerde, en uygun sonuç; 0o açı, 6 lt/dk yıkama suyu ve 200 dev/dk tambur hızında alınmıştır. Buna göre, %14.96 Zn içeren kosantre, %41.61 kazanma verimi elde edilmiştir. Döner diskli manyetik ayırıcıda 5 amperde yapılan deneylerde ise manyetik olmayan üründeki Zn içeriği %20.38, kazanma verimi ise %19.25 olarak belirlenmiştir. Son olarak, pilot tip büyük flotasyon kolonunda optimum koşullarda yapılan temizleme deneylerinde; % 61.22 Pb içeren konsante, % 80.55metal kazanma verimi ile elde edilmiştir.

The objective of this study is the recovery of the ores of oxide, lead and zinc obtained from Zamantı, Kayseri selectively using various techniques. In order to characterize the sample, the chemical, physical and mineralogical properties of the mixing time were determined. The screen analyses show that 65% of the mixing sample remains under 3.36 mm. In addition to this, the chemical analysis shows that the mixing sample consists of 11.50% Zn and 9.81% Pb. As a result of the experiments, the best result for Zn in pre-flotation experiments was obtained at natural pH, under 0.1 mm and 25% of pulp density. The optimum result of the experiments with MGS was obtained at 0o angle, 6 l/min. cleaning water and 200 rpm roll speed. It is gained a concentrate containing 14.96 % Zn with 41.61% recovery. Magnetic recovery using a roll type rare earth magnetic separator at 5 ampere reveals that a non-magnetic product containing 20.38% Zn with the 19.25% recovery was obtained. For the further stage, the optimum conditions were applied to the column with a bigger diameter and the compound that contained 61.22 % Pb with 80.55 % metal productivity ratio was obtained at cleaning experiments performed.
Recovery Of Oxide Lead And Zinc Ores In Zamanti Region
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2002
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2002
Keywords: Oksit Kurşun-Çinko; Kolon Flotasyonu; Multi Gravite Ayırıcısı ve Jones Manyetik Ayırıcısı; Oxide Lead and Zinc; Coloumn Flotation; Multi Gravity Separator and Jones Magnetic Seperator